Comparison between PRIMO and EGSnrc Monte Carlo models of the Varian True Beam linear accelerator. (January 2021) - Aamri, Hussin; Fielding, Andrew; Aamry, Ali; Sulieman, Abdelmoneim; Tamam, Nissren; Alkhorayef, Mohammed; Bradley, David A.
Abstract: The study objectives were to simulate a 6 MV flattening filter-free (FFF) photon beam of a TrueBeam Varian LINAC, using the PRIMO code. The depth-dose profiles for various jaw open fields and cross-beam profiles for various depths inside water phantoms were determined using PRIMO simulations and were compared with the EGSnrc simulation results. A 93% match between both codes has generally been obtained, with a systematic variation in agreement between the two models that increases with field size. The closest agreement, to within 94%, was obtained for a 6 × 6 cm 2 jaw open field at 5.0 cm and 10.0 cm depths, better at 10- than at 5.0 cm depth. The effects of how scatter is modelled has been shown to result in the differences. Highlights: 6 MV flattening filter-free photon beam of a TrueBeam Varian LINAC was simulated. PRIMO code simulations were compared with the EGSnrc simulation results. A 93% match being between both codes has generally been obtained. PRIMO can be successfully used as an alternative code for dosimetric calculations.